Developing Musical Sensitivity and Creativity through Various Forms of Play Activities - Cartagena, Hermie Fuentespina (Malaysian Journal of Music, 2021)
This paper presents the potential of various play activities in developing learner’s musical sensitivity and creativity. The K to12 music education curriculum guide of the Philippine Department of Education advocates the use of experiential learning and outcome-based learning in the classroom. One of the ways in which these methodologies can be promoted is by engaging learners in various play activities. However, there is a lack of literature showing the impact of such methodologies on Filipino learners. Using a priori deductive method, data from a series of interviews, observations, and video and picture analysis from this ethnographic case research were analysed to determine the implications of play activities in classroom music education. The interlocutors of the study are selected Ilonggo children, their parents, and some teachers. This study sought to answer the question of how can play activities be beneficial to classroom music education. Findings suggest that play activities can be a learning tool for the holistic development of the learners. Various forms of play activities provide an avenue for the learners to think or imagine situations divergently and have meaningful musical experiences as they portray various roles. Therefore, play activities provide the learners with a holistic learning experience and the agency to develop their musical sensitivity and creativity.